1998
DOI: 10.1161/01.cir.98.23.2520
|View full text |Cite
|
Sign up to set email alerts
|

Common Methylenetetrahydrofolate Reductase Gene Mutation Leads to Hyperhomocysteinemia but Not to Vascular Disease

Abstract: We conclude that although the C677T/MTHFR mutation is a major cause of mild hyperhomocysteinemia, the mutation does not increase cardiovascular risk. Our findings suggest that the mild hyperhomocysteinemia found frequently in vascular disease patients is not causally related to the pathogenesis of the vascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

30
323
9
25

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 595 publications
(390 citation statements)
references
References 46 publications
30
323
9
25
Order By: Relevance
“…In our study, serum homocysteine concentrations were found significantly higher in pregnant women with the T/T genotype, as compared to those in the C/T or C/C genotype, confirming the results of other investigators (Jacques et al, 1996;Brattstrom et al, 1998;Gudnason et al, 1998). Serum homocysteine was negatively correlated with serum folate in our study subjects of all the three MTHFR genotypes, and the correlation between the two serum levels was strongest as had been previously reported by Ueland et al (2001) and Guttormsen et al (1996), who had observed a steeper negative slope in plots of serum folate vs serum homocysteine concentration in T/T individuals compared to those in the C/T or C/C subjects.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our study, serum homocysteine concentrations were found significantly higher in pregnant women with the T/T genotype, as compared to those in the C/T or C/C genotype, confirming the results of other investigators (Jacques et al, 1996;Brattstrom et al, 1998;Gudnason et al, 1998). Serum homocysteine was negatively correlated with serum folate in our study subjects of all the three MTHFR genotypes, and the correlation between the two serum levels was strongest as had been previously reported by Ueland et al (2001) and Guttormsen et al (1996), who had observed a steeper negative slope in plots of serum folate vs serum homocysteine concentration in T/T individuals compared to those in the C/T or C/C subjects.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, pregnant women who were homozygotes for the MTHFR mutation had higher fasting homocysteine levels only when their serum folate levels were below the median, but not when serum folate levels were above the median. This confirms the study of Brattstrom et al (1998) and Bailey and Gregory III (1999), who reported that the association between the MTHFR genotype and homocysteine levels was modified by serum folate status. One explanation for these observations could be, as hypothesized by Jacques et al (1996), that a higher folate status may increase the in vivo stability of the MTHFR enzyme, thus reducing the difference in enzyme activity between the T/T and C/T or C/C genotype.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The finding of an interaction effect between smoking and MTHFR(C677T) genotype has not been reported previously. A suboptimal plasma folate status among smokers (Piyathilake et al, 1994;Cafolla et al, 2000;O'Callaghan et al, 2002) might explain the observed interaction, as plasma folate has been shown to interact with MTHFR(C677T) genotype (Jacques et al, 1996b;Brattstrom et al, 1998;Girelli et al, 1998;McQuillan et al, 1999;Dekou et al, 2001;Saw et al, 2001). The involvement of folate is further supported by another study in which smoking was reported to interact with the dietary intake of folate (De Bree et al, 2001b).…”
Section: Discussionmentioning
confidence: 99%
“…16 The reported prevalence of the homozygous 677C4T (TT) genotype is between 0 and 32% of the population world-wide, 17 ranging from 5 to 15% in Caucasian populations. 18 The single amino-acid substitution results in impaired flavin adenine dinucleotide (FAD) binding, leading to loss of folate resulting, in its turn, in reduced activity of MTHFR. 19 Subjects with the TT genotype have about 25% higher homocysteine levels than those with the normal homozygous (CC) genotype, 18 whereby the impact of the polymorphism varies according to folate or riboflavin status.…”
Section: Introductionmentioning
confidence: 99%